The reliability of the augmented Lehnert-Schroth and Rigo classification in scoliosis management - KURU ÇOLAK, TUĞBA (AOSIS, 2021)
Background: In pattern-specific scoliosis exercises and bracing, the corrective treatment plan differs according to different curve patterns. There are a limited number of studies investigating the reliability of the commonly used classifications systems. Objective: To test the reliability of the augmented Lehnert-Schroth (ALS) classification and the Rigo classification. Methods: X-rays and posterior photographs of 45 patients with scoliosis were sent by the first author to three clinicians twice at 1-week intervals. The clinicians classified images according to the ALS and Rigo classifications, and the data were analysed using SPSS V-16. Intraclass correlation coefficients (ICCs) and standard error measurement (SEM) were calculated to evaluate the inter-and intra-observer reliability. Results: The inter-observer ICC values were 0.552 (ALS), 0.452 (Rigo) for X-ray images and 0.494 (ALS), 0.518 (Rigo) for the photographs. The average intra-observer ICC value was 0.720 (ALS), 0.581 (Rigo) for the X-ray images and 0.726 (ALS) and 0.467 (Rigo) for the photographs. Conclusions: The results of our study indicate moderate inter-observer reliability for X-ray images using the ALS classification and clinical photographs using the Rigo classification. Intra-observer reliability was moderate to good for X-ray images and clinical photographs using the ALS classification and poor to moderate for X-ray and clinical photographs using the Rigo classification.
Keywords: scoliosis; augmented Lehnert-Schroth classification; Rigo classification; conservative treatment; reliability; IDIOPATHIC SCOLIOSIS; ADOLESCENT